Chronicity of Voice‐Related Health Care Utilization in the General Medicine Community. (7th February 2017) - Cohen, Seth M.; Lee, Hui‐Jie; Roy, Nelson; Misono, Stephanie
Abstract : Objectives: To examine voice‐related health care utilization of patients in the general medical community without otolaryngology evaluation and explore factors associated with prolonged voice‐related health care. Study Design: Retrospective cohort analysis. Setting: Large, national administrative US claims database. Subjects and Methods: Patients with voice disorders per International Classification of Diseases, Ninth Revision, Clinical Modification ( ICD‐9‐CM ) codes from January 1, 2010, to December 31, 2012, seen by a general medical physician, and who did not see an otolaryngologist in the subsequent year were included. Voice‐related health care utilization, patient demographics, comorbid conditions, and index laryngeal diagnosis were collected. Logistic regression with variable selection was performed to evaluate the association between predictors and ≥30 days of voice‐related health care use. Results: In total, 46, 205 unique voice‐disordered patients met inclusion criteria. Of these patients, 8.5%, 10.0%, and 12.5% had voice‐related health care use of ≥90, ≥60, and ≥30 days, respectively. Of the ≥30‐day subset, 80.3% and 68.5%, respectively, had ≥60 and ≥90 days of voice‐related health care utilization. The ≥30‐day subset had more general medicine and nonotolaryngology specialty physician visits, more prescriptions and procedures, and 4 times the voice‐related health care costs compared with those in the <30‐day subset. Age, sex, employment status, initial voice disorder diagnosis, and comorbid conditions were related to ≥30 days of voice‐related health care utilization. Conclusions: Thirty days of nonotolaryngology‐based care for a voice disorder may represent a threshold beyond which patients are more likely to experience prolonged voice‐related health care utilization. Specific factors were associated with extended voice‐related health care.